Uncovering the Burden of Influenza-Associated Illness across Levels of Severity in the Kingdom of Saudi Arabia Across Three Seasons - Amal M. Alshahrani; Ezzualdeen Okmi; Sheena G. Sullivan; Stefano Tempia; Amal Barakat; Hala Abou El Naja; Amir Aman; Osman Hamedelneil; Mutaz Mohamed; Seham F. Basheer; Ghaliah Albugami; Randah Alalweet; et al. (Journal of Epidemiology and Global Health)
Abstract Background Influenza imposes a substantial global health burden, particularly among high-risk populations such as the elderly, young children, and individuals with chronic conditions. In Saudi Arabia, a national influenza sentinel surveillance program was established in 2017 to monitor respiratory virus trends, yet comprehensive estimates of the influenza-associated burden remain limited. This study aims to address this gap by quantifying influenza-associated severe acute respiratory infection (SARI) hospitalization rates and estimating the broader influenza burden across severity levels. Methods Data from four sentinel hospitals in three regions of Saudi Arabia were analyzed across three influenza seasons: 2017–2018, 2018–2019, and 2022–2023. Weekly SARI case counts were combined with census population data to calculate SARI hospitalization rates per 100,000 population. Influenza positivity rates, derived from laboratory-confirmed cases, were used to estimate influenza-associated SARI hospitalization rates, stratified by age and season. The John Hopkins University/WHO Seasonal Influenza Burden Disease Estimator (Flutool) was employed to extrapolate national estimates of influenza-associated hospitalizations, deaths, and mild/moderate cases. Confidence intervals and age-specific stratifications were computed to enhance precision and comparability. Results The average annual SARI hospitalization rate was 294 per 100,000 population (95% CI: 288–300). Influenza-associated SARI hospitalization rates averaged 48 per 100,000 population (95% CI: 45–50), with the highest burden observed in individuals aged 65 years and older (269 per 100,000, 95% CI: 240–301) and children aged 0–4 years (118 per 100,000, 95% CI: 107–131). Seasonal variation was noted, with the highest rates in the 2017–2018 season. National estimates suggested a substantial burden, with influenza-associated hospitalizations totaling 17,678 in 2017–2018, 7,683 in 2018–2019, and 13,982 in 2022–2023. The flutool analysis estimated annual influenza-associated deaths ranging from 30 to 4,441 and mild/moderate cases reaching up to 6.3 million in the most severe season. Conclusions This study demonstrates a significant burden of influenza-associated SARI hospitalizations in Saudi Arabia, with the highest rates observed in the elderly and young children. Seasonal variation was evident, highlighting the urgent need to enhance influenza vaccination coverage, particularly among high-risk groups such as the elderly and young children, to reduce severe outcomes. Expanding sentinel surveillance to more regions and incorporating detailed clinical and economic data are recommended to better inform public health policies. Strengthening pandemic preparedness and tailoring vaccination campaigns based on seasonality and age-specific risk will be critical for mitigating the influenza burden in Saudi Arabia.